2016
DOI: 10.17705/1thci.00078
|View full text |Cite
|
Sign up to set email alerts
|

Website Credibility Assessment: An Empirical - Investigation of Prominence-interpretation Theory

Abstract: Abstract:While a variety of research studies have examined factors that influence individuals' attitudes toward and use of websites, an important yet understudied stream looks at the role of website credibility. We examine website credibility through the lens of prominence-interpretation theory. Fogg (2003) developed this theory to help explain the relationships between what users observe about a website, how they interpret it, and how observation and interpretation together determine website credibility. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Interval (5-point scales) [49] Experience in using accounting information (IOAI_2) Your knowledge of evaluating business performance (IOAI_3) Assistance from finance experts (IOAI_4) Your prior belief in accounting information (IOAI_5)…”
Section: Model Developmentmentioning
confidence: 99%
“…Interval (5-point scales) [49] Experience in using accounting information (IOAI_2) Your knowledge of evaluating business performance (IOAI_3) Assistance from finance experts (IOAI_4) Your prior belief in accounting information (IOAI_5)…”
Section: Model Developmentmentioning
confidence: 99%
“…Research has supported this theory. For instance, George et al (2016) found the prominence of images and visual design meant users were more likely to notice these features and incorporate them in credibility assessments. Howe and Teufel (2014) found younger users were more likely to notice advertising, and subsequently rate sites as less credible, suggesting demographics influenced cue prominence.…”
Section: Information Processing During News Usementioning
confidence: 99%
“…For instance, articles have identified and examined factors crucial to website design [2], defined frameworks for evaluating the quality of websites [3], and conducted user studies (e.g., via eye-tracking) to assess how websites are used and any innate complexities in perceptions [4].…”
mentioning
confidence: 99%